Ludicidade e biblioteca escolar na educação infantil: aplicabilidade de jogos e brincadeiras no incentivo à leitura - Maciel, Letícia de Souza (Brasil, 2024)
The study addresses the inclusion of reading in the daily life of Early Childhood Education, as a strategy studied by psychologists, pedagogues, among other professionals involved in the teaching-learning context. Describing that children in Early Childhood Education need to be well guided and monitored, so that they can develop and create good habits in the school environment. Therefore, the use of games within the school context is relevant, as they contribute to the development of critical skills and the achievement of responsibilities in relation to learning. The general objective of the study is to show the importance of games and games as a resource for the development of reading in Early Childhood Education, characterizing the child, the learning process and playfulness in Early Childhood Education; identifying the role of the school librarian as a mediator of playful activities aimed at encouraging reading in Early Childhood Education; and listing playful activities that can be worked on in BE to develop reading in Early Childhood Education. The methodological path used was bibliographic and documentary research, descriptive and exploratory in nature with a qualitative focus. Therefore, the importance of the physical space of the library in relation to reading is evident, determining the need to have the perspective of a reader or user and maintain a focus on both intellectual satisfaction and the development of reading and writing skills and motivation. through the act of reading through playful strategies.